Challenging Institutions: Getting Goods or Getting Your Own Institution? - Millard, Matt (Journal of Regional Security, 2018)
I present a discussion of the current state of liberal internationalism as it relates to international organisations. I maintain that the literature focuses too much on liberal interna- tionalism instead of non-liberal internationalism. This is problematic because non-liberal states are increasingly becoming important players in the international system, as is the case with Rus- sia and China. I argue that non-liberal states have a variety of approaches in their dealings with international institutions that can enable them to maximise their net gains from institutions. These are: 1) keep using the liberal institution, 2) utilise institutional àla cartism (forum shop- ping), 3) create an anti-liberal institution, or 4) opt out of institutions alltogether. Scholars and practitioners alike should acknowledge that international institutions can be a vehicle whereby non-liberal states maximise their power and diminish the power and influence of liberal states.